Less is more: strategies to remove marker genes from transgenic plants - Yau, Yuan-Yeu (BioMed Central, 2013)
Selectable marker genes (SMGs) and selection agents are useful tools in the production of transgenic plants by selecting transformed cells from a matrix consisting of mostly untransformed cells. Most SMGs express protein products that confer antibiotic- or herbicide resistance traits, and typically reside in the end product of genetically-modified (GM) plants. The presence of these genes in GM plants, and subsequently in food, feed and the environment, are of concern and subject to special government regulation in many countries. The presence of SMGs in GM plants might also, in some cases, result in a metabolic burden for the host plants. Their use also prevents the re-use of the same SMG when a second transformation scheme is needed to be performed on the transgenic host. In recent years, several strategies have been developed to remove SMGs from GM products while retaining the transgenes of interest. This review describes the existing strategies for SMG removal, including the implementation of site specific recombination systems, TALENs and ZFNs. This review discusses the advantages and disadvantages of existing SMG-removal strategies and explores possible future research directions for SMG removal including emerging technologies for increased precision for genome modification.